The effects of low temperature on the growth and total protein amount of chickpea (Cicer arietinum) seedlings - Munzuro?lu, O.; Zengin, F. (Akademiai Kiado Rt., 2001)
In this study, shocks of cold at the levels of 5,3 and 1 °C have been applied to the 6-days old chickpea (Cicer arietinum L.) plants. Next, having been left to grow for 72 hours under long day photoperiod circumstances at 25 °C, the length of their root and epicotyl have been measured at certain intervals. Moreover, the protein contents of the plants exposed to low temperature shocks (1 °C) have been identified in connection with their controls. According to the results obtained, the low temperature shocks have prevented the length of the roots and epicotyl to a large extent. It is observed that the lower the temperature is, the more the plant's growth is prevented. It has also been observed that the cold stress caused by the low temperature application might be reversible. The plants get rid of this stress later in low temperatures than in high ones. The low temperature application (1 °C) has also considerably reduced the total protein amount. © 2001 Akadémiai Kiadó.
Keywords: Chickpea (Cicer arietinum L.); Low temperature shock (chilling effect); Plant growth; Protein